واقع الرقابة الشرعية والتدقيق الشرعي في المؤسسات المالية الإسلامية - زيان، يوسف (جامعة الوادي University of Eloued, 2025)
تهدف هده الدراسة إلى معرفة واقع الرقابة الشرعية والتدقيق الشرعي في المصارف الإسلامية دراسة حالة بنك البركة الجزائري 2023، بحيث تعتبر الرقابة الشرعية والتدقيق الشرعي عنصرين أساسين في إعطاء حكم على صحة ومصداقية معاملات والمنتجات المقدمة من طرف المؤسسة المالية ومطابقتها لأحكام الشريعة. وخلصت الدراسة إلى وجود في بنك البركة هيئة الرقابة الشرعية مكلفة بعمل الرقابة والتدقيق وفقا للشريعة، بحيث تم تأكيد بأن إجراءات التي طبقها البنك في سنة 2023 قد تمت وفقا لأحكام الشريعة الإسلامية مع وجود مداخيل غير موافق للشريعة يتم صرفها في سبل الخيرات. This study aims to know the reality of Sharia control and Sharia audit in Islamic financial institutions, the study of Al-Baraka Algerian Bank 2023, as Shari'ah supervision and Shari'ah auditing are two key elements in giving a judgment on the validity and credibility of transactions and products provided by the financial institution and their conformity with the provisions of Shari'ah . The study concluded that Al Baraka Bank has a Shari'ah Supervisory Board in charge of monitoring and auditing in accordance with Shari'ah, so that it was confirmed that the procedures applied by the bank in 2023 were carried out in accordance with the provisions of Islamic Shari'ah with the presence of non-Shari'ahcompliant income to be spent in ways of goodness.
The Reality of Shari'a Supervision and Shari'a Audit in Islamic Financial Institutions Al Baraka Bank in 2023
مقال
Keywords: الرقابة الشرعية; التدقيق الشرعي; المصارف الإسلامية; بنك البركة; هيئة الرقابة الشرعية; Shari'ah Supervision; Shari'ah Audit; Islamic Banks; Al Baraka Bank; Sharia Supervisory Board